POTENTIAL BENEFITS, CHALLENGES, AND BUSINESS MODEL OF CLOUD LEARNING: A CASE STUDY OF INDONESIA - Baginda Anggun Nan Cenka; Harry B. Santoso; Nungki Selviandro (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2012)
During the last years, the most of educational institution have applying e-learning, however it is becoming not in line for social changes and educational progress. Hence, redesign the educational system is strong required. At the same time, Cloud computing is growing rapidly and created a global phenomenon on Information and Communication Technology (ICT) which playing cross over in any area, including education and often called Cloud Learning. In this paper we elaborate why cloud learning is widely accepted today, what considerable risk when adopting this practices, and what about the business model on Cloud Learning.